Application of the Supply Chain Operation Reference (SCOR) Method: Batik SMEs in Indonesia - Kasmari, Fransiskus; Basukiyanto, Basukiyanto; Indriyaningrum, Kis (International Journal of Supply Chain Management, 2020)
ABSTRACTÂ This study aims to determine the results of SCM performance measurement with the Supply Chain Operation Reference (SCOR) approach at Batik SMEs in Indonesia. The steps in this research are the creation of a hierarchy of variables in SCOR, namely Plan, Source, Make, Delivery, and Return. From these variables derived into dimensions, namely, Reliability, Responsiveness, Flexibility, Cost, and Assets. The variables and dimensions are adjusted to the condition of the company which is then carried out to measure the company's SCM performance. Then the benchmarks are made in the measurement by way of Key Performance Indicator identification (KPI). The next step is to normalize Snorm De Boer which functions to equalize the KPI values. Analytical Hierarchy Process (AHP) is carried out next to assist in determining the priority of existing criteria. The results of the measurement of SCM performance in Batik SMEs in Indonesia from 24 KPI and produce the highest performance value in the Make process of 30.74 while the lowest value is a Return of 6.33. The company's SCM performance value is 89.08. This value indicates that the company's SCM performance achievement is classified as Excellent.Keywords- Key Performance Indicator, Analytical Hierarchy Process, Supply Chain Management, and Supply Chain Operation Reference